(untitled) (Marketing Jurnali, 2024)
In this paper conducted econometric analysis to estimate role of agriculture sector in socio-economic development of Khorezm region. Used coefficient of elasticity for assessing role of agriculture sector to GRP, real income and employment. Based on the results, developed scientific-practical proposals and recommendations to increase role of agriculture sector on employment and real income.